Neonatal minimal invasive management of a prenatal gunshot trauma: case report - Camila Gonzalez Ruhrnschopf; Aixa Reusmann; Mariano Boglione; Soledad Arbio; Marcelo Barrenechea (SpringerOpen, 2021)
Abstract Background Prenatal penetrating gunshot trauma represents a challenging scenario for healthcare providers. Trauma is the leading non-obstetric cause of morbidity and mortality during pregnancy, and even though rare, firearm injuries have the most fatal outcomes and higher fetus mortality rates. Understanding the mechanism of injury in order to identify the possible injuries and adequate management is essential. In this paper, we discuss the case of a newborn with prenatal gunshot trauma, the treatment used, and the outcome of conservative and minimally invasive management. Case presentation We present the case of a male newborn, 37 weeks of gestational age and weighing 3050 g, delivered through an emergency cesarean section with prenatal gunshot trauma. Two skin wounds were found, one in the arm and another in the left thoracic region. The patient presented with respiratory distress, bilateral pneumothorax, and pneumoperitoneum, requiring high-frequency mechanical ventilation and the placement of bilateral thoracic drains. The pneumoperitoneum was attributed to pulmonary barotrauma, with no suspicion of abdominal hollow viscera lesion. A right thoracoscopy was performed after 24 h of conservative management for the removal of the foreign body. Both the mother and the baby had a positive outcome, with no further treatment needed. Conclusions For the improvement in the result of trauma events, an adequate intervention and coordinated efforts from multidisciplinary clinical and surgical teams are required. For gunshot wounds, entry, trajectory, the final position of the bullet, and pathological findings in images need to be analyzed before taking the patient to the operative room. Chosen with strict selection criteria, some patients could benefit from conservative management.